2022
DOI: 10.1055/s-0042-1751008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Magnetic Resonance Imaging (i-MRI) on Surgeon Decision Making and Clinical Outcomes in Cranial Tumor Surgery

Abstract: Background Although intraoperative magnetic resonance imaging (iMRI) has an established role in guiding intraoperative extent of resection (EOR) in cranial tumor surgery, the details of how iMRI data are used by the surgeon in the real-time decision-making process is lacking. Materials and Methods The authors retrospectively reviewed 40 consecutive patients who underwent cranial tumor resection with the guidance of iMRI. The tumor volumes were measured by volumetric software. Intraoperative and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In our study, 36% (45/125) of patients in the Io MRI group were returned to the operating room, increasing the resection rates. In a similar study by Bunyaratavej et al that included glioma and non-glioma diagnoses, this rate was found to be 60% (24/40) [11]. These results show that the use of Io MRI in brain tumor surgery offers the possibility of an additional excision during the same surgical procedure in the event that the surgeon did not anticipate residual tumor before the operation.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, 36% (45/125) of patients in the Io MRI group were returned to the operating room, increasing the resection rates. In a similar study by Bunyaratavej et al that included glioma and non-glioma diagnoses, this rate was found to be 60% (24/40) [11]. These results show that the use of Io MRI in brain tumor surgery offers the possibility of an additional excision during the same surgical procedure in the event that the surgeon did not anticipate residual tumor before the operation.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, 36% (45/125) of patients in the Io MRI group were returned to the operating room, increasing the resection rates. In a similar study by Bunyaratavej et al that included glioma and non - glioma diagnoses, this rate was found to be 60% (24/40) [ 13 ]. These results show that the use of Io MRI in brain tumor surgery offers the possibility of an additional excision during the same surgical procedure in the event that the surgeon did not anticipate residual tumor before the operation.…”
Section: Discussionmentioning
confidence: 99%